Analisis Kebutuhan Dan Perancangan Platform E-Learning Untuk Meningkatkan Akses Pendidikan Masyarakat Desa Hiliserangkai - Febrianus Halawa; Albert Elisman Zalukhu; Hengki Kurniawan Ndruru; Jurisman Waruwu (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
The rapid development of information technology has created new opportunities to improve educational access, especially for rural communities. However, limitations in learning resources and digital literacy remain challenges for many villages, including Hiliserangkai Village. This study aims to analyze community needs and design an e-learning platform that can support educational access through basic Artificial Intelligence (AI) learning materials. The study employed the Research and Development (R&D) method, consisting of problem identification, data collection, needs analysis, platform design, AI learning content design, design validation, and report preparation. Data were collected through observation and interviews involving 30 community members as respondents. The findings indicate that 86.7% of respondents require digital learning media, 83.3% frequently access the internet using smartphones, and 90% show interest in learning AI through simple and interactive learning materials. Based on these findings, a web-based e-learning platform was designed with features including user registration, login, AI learning materials, educational videos, quizzes, and administrator management functions. The proposed platform is expected to enhance educational accessibility and support digital literacy development among rural communities. Furthermore, the design can serve as a foundation for future implementation and development of educational technology systems in rural areas.